2012
DOI: 10.1371/journal.pone.0045405
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiangiogenic Activity of N-Alkylated Levamisole Derivatives

Abstract: Inhibition of angiogenesis is a promising addition to current cancer treatment strategies. Neutralization of vascular endothelial growth factor by monoclonal antibodies is clinically effective but may cause side effects due to thrombosis. Low molecular weight angiogenesis inhibitors are currently less effective than antibody treatment and are also associated with serious side effects. The discovery of new chemotypes with efficient antiangiogenic activity is therefore of pertinent interest. (S)-Levamisole hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…3) for the in vitro inhibition of angiogenesis. 81 The authors summarized the morphological effect of the three groups of This journal is © The Royal Society of Chemistry 2017 levamisole. In the first group, the authors found p-bromolevamisole 2 was an equivalent angiogenic agent to levamisole, and N-methyllevamisoles 4a and 4b were more potent than the parent inhibitor, levamisole.…”
Section: Imidazoles As Antiangiogenic Agentsmentioning
confidence: 99%
“…3) for the in vitro inhibition of angiogenesis. 81 The authors summarized the morphological effect of the three groups of This journal is © The Royal Society of Chemistry 2017 levamisole. In the first group, the authors found p-bromolevamisole 2 was an equivalent angiogenic agent to levamisole, and N-methyllevamisoles 4a and 4b were more potent than the parent inhibitor, levamisole.…”
Section: Imidazoles As Antiangiogenic Agentsmentioning
confidence: 99%
“…It inhibits the proliferation, the differentiation, and capillary network formation of endothelial cells in vitro [ 5 ]. Levamisole derivatives disrupt endothelial network formation less efficiently than levamisole itself [ 6 ]. Levamisole has been reported to induce apoptosis in cultured endothelial cells [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Levamisole has previously shown inhibition of angiogenesis in vitro, when HUVECs were propagated on NHDFs, and inhibition of tumor growth in vivo [30,31]. Levamisole and various derivatives were tested at 1 mM and 100 µM, respectively, which were the highest concentrations with an inhibitory effect without being lethal (Figure 3).…”
Section: Levamisole and Its Derivativesmentioning
confidence: 99%